Social intermediation and financial services access in Uganda’s microfinance industry - Kamukama, Nixon; Natamba, Bazinzi (African Journal of Economic and Management Studies, 2013)
Purpose: The purpose of this paper is to examine the extent to which social intermediation influences access to financial services in Uganda’s microfinance industry. Design/methodology/approach: The paper adopts analysis of moment structures (AMOS), a form of structural equation modeling (SEM) to test hypotheses. Findings: It was established that social intermediation together with antecedents of social capital and managerial competence, account for 32 percent of the variance in access to financial services in the microfinance industry. Research limitations/implications: Only a single research methodological approach was employed and future research through interviews could be undertaken to triangulate. Furthermore, the findings from the present study are cross-sectional, future research should be undertaken to examine the social intermediation and its effects on access to financial services across time. Practical implications: In order to boost the wealth of the active poor and microfinance institutions in Uganda, Uganda should always endeavor to build the human and institutional capacities through social intermediation so as to encourage the marginalized people to fully participate in formal financial intermediation in the microfinance industry. Originality/value: This is the first study that focuses on testing the influence of social intermediation on access to financial services in Uganda’s microfinance industry
Keywords: Social intermediation; Microfinance industry; Access to financial services; Uganda; Finance